Cement composition and hydraulic composition
Patent Information
- Application Number
- JP2024522670
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-12-12
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2043-12-12
AI Technical Summary
【0010】 本発明のセメント組成物は、水を加えて硬化体とするときに、強度発現性に優れたものである。 また、本発明のセメント組成物は、水を加えて硬化物とする際の養生過程において炭酸化養生等を行うことによって、多量の二酸化炭素を吸収、固定化することにより、排出される二酸化炭素の総量を低減することができる。 さらに、本発明のセメント組成物を構成する(ii)焼成物の粉砕物の原料組成を調整し、ポルトランドセメントに比べて、CaOの含有率を小さくすることによって、製造時の二酸化炭素の排出量を削減することができる。また、上記焼成物の製造時の焼成温度を、ポルトランドセメントの製造時の焼成温度に比べて低くすることによって、焼成用の燃料から生じる二酸化炭素の排出量を削減することができる。
Smart Images

Figure 0007636636000001 
Figure 0007636636000002 
Figure 0007636636000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cement composition and a hydraulic composition containing the cement composition. [Background technology]
[0002] Currently, reducing carbon dioxide emissions has become an important issue in order to curb global warming. As a method for reducing the amount of carbon dioxide emitted in the production of a cementitious hardened body, a method is known in which carbon dioxide is absorbed during the curing process of the cementitious hardened body, thereby reducing the total amount of carbon dioxide emitted until the cementitious hardened body is obtained. Patent Document 1 describes a cementitious hardened body that can absorb a large amount of carbon dioxide during the curing process and thereby significantly reduce the total amount of carbon dioxide emitted, which is obtained by carbonating a hardened body of a cement mixture that contains (A) a powder for cement mixing containing either one or both of mullite and anorthite, and a powdered cement composition containing Portland cement, (B) water, and (C) aggregate. Patent Document 2 describes a cementitious hardened body that can significantly reduce the total amount of carbon dioxide emitted by absorbing a large amount of carbon dioxide during the curing process and has a small rate of decrease in compressive strength when compared to a case in which the entire powder material is made of Portland cement. The cementitious hardened body is characterized by being obtained by carbonating a hardened body of a cement mixture containing: (A) a pulverized product of a fired product containing 10 to 200 parts by mass of C2AS per 100 parts by mass of C2S and having a C3A content of 20 parts by mass or less, a powdered cement composition containing Portland cement, (B) water, and (C) aggregate.
[0003] On the other hand, a cement composition using a pulverized burned material (not corresponding to pulverized cement clinker) as a cement admixture is known. For example, Patent Document 3 describes a fired product (cement admixture) that can reduce the heat of hydration of cement and improve fluidity, which is characterized by containing 10 to 100 parts by weight of C2AS relative to 100 parts by weight of C2S and having a C3A content of 20 parts by weight or less. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-153357 A [Patent Document 2] JP 2016-47788 A [Patent Document 3] JP 2004-2155 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a cement composition which contains a pulverized calcined product (not corresponding to pulverized cement clinker) as a cement admixture, has excellent strength development properties, and is capable of reducing the total amount of carbon dioxide emitted by absorbing and fixing a large amount of carbon dioxide during the curing process, and a hydraulic composition which contains the cement composition. [Means for solving the problem]
[0006] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned objects can be achieved by (A)(i) a powdered cement-containing material containing Portland cement or pulverized Portland cement clinker, and (ii) a pulverized product of a fired material that contains 2CaO·SiO2 and 2CaO·Al2O3·SiO2 and satisfies specific conditions, and (B)(iii) a cement composition containing an amine, and have completed the present invention. That is, the present invention provides the following [1] to
[15] . [1] (A) a powdered cement-containing material comprising (i) ground Portland cement or ground Portland cement clinker, and (ii) a ground product of a fired product containing 2CaO·SiO2 and 2CaO·Al2O3·SiO2, the ground product satisfying the following conditions (1) and (2): (1) The amount of the 2CaO·Al2O3·SiO2 is 10 to 100 parts by mass relative to 100 parts by mass of the 2CaO·SiO2. (2) The calcined product does not contain 3CaO·Al2O3 or contains 15 parts by mass or less of 3CaO·Al2O3 per 100 parts by mass of the 2CaO·SiO2. [2] The cement composition according to [1], wherein the powdered cement-containing material contains (iv) an alkaline earth metal-containing material, and the content of alkaline earth metals in the powdered cement-containing material (wherein the alkaline earth metals other than alkaline earth metals contained in the alkaline earth metal-containing material include only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide) is 0.1 to 10 mass % calculated as oxide. [3] The cement composition according to [1] or [2], wherein the amount of the amine is 0.001 to 5.0 parts by mass per 100 parts by mass of the powdered cement-containing material. [4] The cement composition according to any one of [1] to [3], wherein the amine is an alkanolamine. [5] The cement composition according to any one of [1] to [4], wherein the content of the pulverized product of the fired product in the powdered cement-containing material is 10 to 90 mass %.
[0007] [6] A cement composition comprising: (i) ground Portland cement or ground Portland cement clinker; (ii) a ground fired product containing 2CaO·SiO2 and 2CaO·Al2O3·SiO2, the ground fired product satisfying the following conditions (1) and (2); and (iv) an alkaline earth metal-containing substance, wherein the content of alkaline earth metals in the cement composition (wherein the alkaline earth metal-containing substance includes only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide other than alkaline earth metals) is 0.1 to 10 mass % in terms of oxide. (1) The amount of the 2CaO·Al2O3·SiO2 is 10 to 100 parts by mass relative to 100 parts by mass of the 2CaO·SiO2. (2) The calcined product does not contain 3CaO·Al2O3 or contains 15 parts by mass or less of 3CaO·Al2O3 per 100 parts by mass of the 2CaO·SiO2. [7] The cement composition according to [6], wherein the content of the pulverized fired product in the cement composition is 10 to 90 mass %. [8] The cement composition according to [6] or [7], wherein the alkaline earth metal is magnesium (Mg). [9] The cement composition according to any one of [6] to [8], wherein the alkaline earth metal is calcium (Ca).
[0008]
[10] A hydraulic composition comprising the cement composition according to any one of [1] to [5], water, and an aggregate, wherein the amount of the water is 25 to 70 parts by mass per 100 parts by mass of the powdered cement-containing material.
[11] The hydraulic composition according to the above
[10] , which is a carbonated hardened body obtained by carbonation curing.
[12] A hydraulic composition comprising the cement composition according to any one of [6] to [9], water, and an aggregate, wherein the amount of the water is 25 to 70 parts by mass per 100 parts by mass of the cement composition.
[13] The hydraulic composition according to the above
[12] , which is a carbonated hardened body obtained by carbonation curing.
[0009]
[14] A method for producing the hydraulic composition described in
[11] above, comprising: a mixture preparation step of preparing a mixture, which is a mixture of the materials constituting the cement composition, the water, and the aggregate; a casting step of casting the mixture into a formwork; a demolding step of removing a hardened body of the kneaded material from the formwork after the kneaded material in the formwork has hardened; and a carbonation curing step of carbonating and curing the hardened body of the kneaded material demolded from the formwork to obtain the carbonated hardened body.
[15] A method for producing the hydraulic composition described in
[13] above, comprising: a mixture preparation step of preparing a mixture, which is a mixture of the materials constituting the cement composition, the water, and the aggregate; a casting step of casting the mixture into a formwork; a demolding step of removing a hardened body of the kneaded material from the formwork after the kneaded material in the formwork has hardened; and a carbonation curing step of carbonating and curing the hardened body of the kneaded material demolded from the formwork to obtain the carbonated hardened body. Effect of the Invention
[0010] The cement composition of the present invention exhibits excellent strength development when it is hardened by adding water. In addition, the cement composition of the present invention can absorb and fix a large amount of carbon dioxide by carrying out carbonation curing or the like in the curing process when water is added to form a hardened product, thereby reducing the total amount of carbon dioxide emitted. Furthermore, by adjusting the raw material composition of the (ii) ground fired product constituting the cement composition of the present invention and reducing the CaO content compared to Portland cement, it is possible to reduce the amount of carbon dioxide emitted during production. Also, by lowering the firing temperature during production of the fired product compared to the firing temperature during production of Portland cement, it is possible to reduce the amount of carbon dioxide emitted from the fuel used for firing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Cement composition A] An example of the cement composition of the present invention is (A) a powdered cement-containing material including (i) ground Portland cement or ground Portland cement clinker, and (ii) a ground product of a fired product containing 2CaO·SiO2 (hereinafter also referred to as "C2S") and 2CaO·Al2O3·SiO2 (hereinafter also referred to as "C2AS"), the ground product satisfying the following conditions (1) and (2), and (B) (iii) an amine (hereinafter also referred to as "cement composition A"). (1) The amount of the 2CaO·Al2O3·SiO2 is 10 to 100 parts by mass relative to 100 parts by mass of the 2CaO·SiO2. (2) The calcined product does not contain 3CaO·Al2O3 (hereinafter also referred to as "C3A") or contains it in an amount of 15 parts by mass or less per 100 parts by mass of the 2CaO·SiO2. The details are explained below.
[0012] [Component (A): Powdered cement-containing material] The powdered cement-containing material includes (i) ground Portland cement or ground Portland cement clinker, and (ii) ground fired material containing 2CaO·SiO2 and 2CaO·Al2O3·SiO2, which satisfies the above conditions (1) and (2). [Component (i): Portland cement or ground Portland cement clinker] Examples of Portland cement include various types of Portland cement such as ordinary Portland cement, high early strength Portland cement, moderate heat Portland cement, and low heat Portland cement. Examples of the pulverized Portland cement clinker include pulverized clinker of the various Portland cements mentioned above. These may be used alone or in combination of two or more. Among these, from the viewpoints of cost and versatility, pulverized ordinary Portland cement or pulverized ordinary Portland cement clinker is preferred. The Blaine specific surface area of Portland cement or pulverized Portland cement clinker is preferably 2,500 to 5,000 cm 2 / g, more preferably 3,000 to 4,500 cm 2 / g. The above Blaine specific surface area is 2,500 cm 2 / g or more, the strength development of the cement composition is further improved. 2 / g or less, the fluidity of the cement composition before hardening is further improved.
[0013] The content of Portland cement or pulverized Portland cement clinker in the powdered cement content is preferably 10 to 70 mass%, more preferably 15 to 60 mass%, further preferably 20 to 50 mass%, and particularly preferably 25 to 40 mass%. If the content is 10 mass% or more, the strength of the hardened body of the hydraulic composition can be further increased. If the content is 60 mass% or less, the content of (ii) the pulverized calcined product becomes larger, and the reduction in the carbon dioxide emissions described above can be further achieved. The content of Portland cement or ground Portland cement clinker in the cement composition A is preferably 10 to 70% by mass, more preferably 15 to 60% by mass, even more preferably 20 to 50% by mass, and particularly preferably 25 to 40% by mass. If the content is 10% by mass or more, the strength of the hardened body can be increased. If the content is 60% by mass or less, the content of (ii) ground fired material becomes larger, and the reduction in carbon dioxide emissions can be further achieved.
[0014] [Component (ii): Crushed fired material containing C2S and C2AS] In a fired product containing C2S and C2AS (hereinafter, simply referred to as "fired product"), the amount of C2AS relative to 100 parts by mass of C2S is 10 to 100 parts by mass, preferably 20 to 80 parts by mass, more preferably 25 to 70 parts by mass, and particularly preferably 30 to 60 parts by mass. In a fired product in which the amount is less than 10 parts by mass, the carbonation of the hydraulic composition (e.g., mortar) during carbonation curing is difficult to proceed, and the amount of carbon dioxide absorbed at an early age is reduced. When the amount exceeds 100 parts by mass, the amount of C2S is relatively reduced, so that the strength development of the cement composition is reduced and the amount of carbon dioxide absorbed by the hydraulic composition at a long age is reduced. When the fired product contains C3A, the amount of C3A relative to 100 parts by mass of C2S is 15 parts by mass or less, preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass. If the amount exceeds 15 parts by mass, it is difficult to produce the fired product. If the amount is 15 parts by mass or less, the fluidity of the hydraulic composition before hardening is further improved.
[0015] The fired product may contain 4CaO·Al2O3·Fe2O3 (hereinafter also referred to as "C4AF"). The amount of C4AF relative to 100 parts by mass of C2S is preferably 30 parts by mass or less, more preferably 0.1 to 20 parts by mass, further preferably 0.5 to 15 parts by mass, and particularly preferably 1.0 to 10 parts by mass. When the amount is 30 parts by mass or less, the hydration activity of the hydraulic composition at an early age can be further improved. The total amount of C4AF and C2AS relative to 100 parts by mass of C2S is preferably 10 to 100 parts by mass, more preferably 20 to 90 parts by mass, and particularly preferably 30 to 80 parts by mass. When the amount is 10 parts by mass or more, the calcined product is more likely to undergo carbonation of the hydraulic composition (e.g., mortar) during carbonation curing, and the amount of carbon dioxide absorbed at an early age is greater. When the amount is 100 parts by mass or less, the amount of C2S is relatively large, so that the strength development of the cement composition is improved and the amount of carbon dioxide absorbed by the hydraulic composition at a long age is greater. The amount of C4AF relative to 100 parts by mass of C2AS is preferably 210 parts by mass or less, more preferably 100 parts by mass or less, further preferably 50 parts by mass or less, and particularly preferably 20 parts by mass or less. If the amount is 210 parts by mass or less, the hydration activity of the hydraulic composition at an early age can be further improved.
[0016] The content of C2S (belite) in the fired product is preferably 50 to 80 mass%, more preferably 55 to 75 mass%, and particularly preferably 60 to 70 mass%. If the content is 50 mass% or more, the long-term strength development of the cement composition is further improved. If the content is 80 mass% or less, the initial strength development of the cement composition is further improved. The content of C2AS in the fired product is preferably 10-60% by mass, more preferably 20-50% by mass, and particularly preferably 25-40% by mass. If the content is 10% by mass or more, the carbonation of the hydraulic composition is facilitated, and the hydraulic composition absorbs more carbon dioxide at an early age. If the content is 60% by mass or less, the amount of C2S is relatively large, so that the strength development of the cement composition is improved and the hydraulic composition absorbs more carbon dioxide at a long age.
[0017] The content of C3A (aluminate phase) in the fired product is preferably 10 mass% or less, more preferably 0.1 to 5 mass%, and particularly preferably 0.5 to 3.5 mass%. If the content is 10 mass% or less, the fluidity of the hydraulic composition before hardening is further improved. The content of C4AF (ferrite phase) in the fired product is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less. If the content is 20% by mass or less, the hydration activity of the hydraulic composition at an early age can be further improved. The content of C3S (alite; 3CaO SiO2) in the fired product is preferably 5 mass% or less, more preferably 3 mass% or less, and particularly preferably 1 mass% or less. If the content is 5 mass% or less, the fluidity of the hydraulic composition before hardening can be further improved.
[0018] The CaO content in the fired product (particularly when limestone is used as a raw material) is preferably 50 to 59 mass%, more preferably 52 to 58 mass%, and particularly preferably 53 to 57 mass%. If the above ratio is 50 mass% or more, the strength development of the cement composition is improved. If the above content is 59 mass% or less, the amount of carbon dioxide emitted during firing can be further reduced. The SiO2 content in the fired product is preferably 15 to 45 mass %, more preferably 20 to 40 mass %, and particularly preferably 25 to 35 mass %. The content of Al2O3 in the fired product is preferably 1 to 10 mass %, more preferably 3 to 9 mass %, and particularly preferably 4 to 8 mass %. The content of Fe2O3 in the fired product is preferably 1 to 8 mass %, more preferably 2 to 6 mass %, and particularly preferably 3 to 5 mass %.
[0019] The mineral composition of the fired product (contents of C2S, C2AS, C3A, and C4AF, etc.) can be quantified by X-ray diffraction (XRD) / Rietveld analysis, etc., for the fired product. Specifically, the theoretical profile of each mineral can be fitted to the powder X-ray diffraction chart (actually measured profile) of the fired product, and quantified by Rietveld analysis. For this quantification, commercially available analysis software can be used. The mineral composition can also be quantified by microscopic observation or point counting using electron backscatter diffraction, etc.
[0020] The above-mentioned fired product can be produced, for example, by preparing the raw material from one or more materials selected from industrial waste, general waste, construction waste soil, etc. so as to have the target mineral composition, chemical composition, etc. of the fired product, and then firing the raw material at, for example, 1,000 to 1,400°C (preferably 1,200 to 1,400°C, and more preferably 1,300 to 1,400°C). In addition, if it is difficult to adjust the mineral composition of the fired material to the target values using only the above raw materials, raw materials such as a calcium raw material (e.g., limestone), a silicon raw material, an aluminum raw material, and an iron raw material may be used. The obtained fired product is appropriately pulverized using a pulverizer such as a ball mill or a rod mill. When the powdered cement-containing material contains gypsum, the fired product and the gypsum may be pulverized and mixed at the same time. The Blaine specific surface area of the fired product is preferably 2,500 to 5,000 cm. 2 / g, more preferably 3,000 to 4,500 cm 2 / g. The above Blaine specific surface area is 2,500 cm 2 / g or more, the hydration reaction is accelerated, the amount of carbon dioxide absorbed is increased, and the strength development of the cement composition is improved. 2 When the viscosity is 100 / g or less, the fluidity of the hydraulic composition before hardening is further improved.
[0021] The content of the pulverized calcined product in the powdered cement-containing material is preferably 10 to 90% by mass, more preferably 30 to 85% by mass, even more preferably 40 to 80% by mass, even more preferably 50 to 80% by mass, and particularly preferably 60 to 80% by mass. If the content is 10% by mass or more, the amount of carbon dioxide absorbed by the hydraulic composition at the initial age is increased. If the amount is 90% by mass or less, the amount of Portland cement or pulverized Portland cement clinker becomes relatively small, which makes it difficult for the strength development of the cement composition to decrease. The amount of the pulverized burned material relative to 100 parts by mass of Portland cement or pulverized Portland cement clinker is preferably 65 to 500 parts by mass, more preferably 100 to 400 parts by mass, even more preferably 150 to 350 parts by mass, and particularly preferably 200 to 320 parts by mass. If the amount is 65 parts by mass or more, the amount of carbon dioxide absorbed by the hydraulic composition at the early age becomes larger. If the amount is 500 parts by mass or less, the strength development of the cement composition is less likely to decrease due to the relatively small amount of Portland cement or pulverized Portland cement clinker.
[0022] The content of the pulverized calcined product in the cement composition is preferably 10 to 90% by mass, more preferably 30 to 85% by mass, even more preferably 40 to 80% by mass, even more preferably 50 to 80% by mass, and particularly preferably 60 to 80% by mass. If the content is 10% by mass or more, the amount of carbon dioxide absorbed by the hydraulic composition at the initial age is increased. If the amount is 90% by mass or less, the amount of Portland cement or pulverized Portland cement clinker is relatively small, which makes it difficult for the strength development of the cement composition to decrease. The ratio of the total amount of component (i) and component (ii) in the (A) powdered cement-containing material is preferably 80 mass% or more, more preferably 90 mass% or more, and particularly preferably 95 mass% or more, from the viewpoint of improving the strength development of the cement composition and increasing the amount of carbon dioxide absorption.
[0023] [Component (iv): Alkaline earth metal-containing material] The powdered cement-containing material may contain (iv) an alkaline earth metal-containing material. When the powdered cement-containing material contains an alkaline earth metal-containing material, the strength development of the cement composition can be further improved. Examples of alkaline earth metals contained in the alkaline earth metal-containing material include calcium (Ca), magnesium (Mg), strontium (Sr), barium (Ba), radium (Ra), and beryllium (Be), etc. These may be contained alone or in combination of two or more. Among these, from the viewpoints of strength development of the cement composition, ease of availability, and the like, calcium (Ca) and magnesium (Mg) are preferred, and magnesium (Mg) is more preferred. From the viewpoint of improving the strength development of the cement composition, the form of the alkaline earth metal contained in the cement composition is preferably an alkaline earth metal oxide or an alkaline earth metal hydroxide, and more preferably an alkaline earth metal oxide.
[0024] When the alkaline earth metal-containing material contains magnesium as the alkaline earth metal, examples of the magnesium source (magnesium-containing substance) include magnesium oxide, magnesium hydroxide, magnesium sulfate, magnesium nitrate, magnesium chloride, etc. Among them, from the viewpoint of further improving the strength development of the cement composition, magnesium oxide and magnesium hydroxide are preferred, and magnesium oxide is more preferred. These may be reagents, or may be magnesium-containing substances such as periclase (a mineral containing magnesium oxide), light-burned magnesia (MgO), partial hydrate of light-burned magnesia, light-burned dolomite (CaO·MgO), and partial hydrate of light-burned dolomite. These may be used alone or in combination of two or more.
[0025] Examples of the calcium source (calcium-containing substance) when the alkaline earth metal-containing material contains calcium as the alkaline earth metal include calcium oxide, calcium hydroxide, calcium nitrate, and calcium chloride. These may be reagents, or may be calcium-containing substances such as quicklime, slaked lime, ready-mixed concrete sludge, and waste concrete. These may be used alone or in combination of two or more. Among them, calcium oxide and calcium hydroxide are preferred, and calcium oxide is more preferred, from the viewpoint of further improving the strength development of the cement composition. The ready-mixed concrete sludge is preferably a powdered form obtained by sifting sludge generated in the concrete manufacturing process at a ready-mixed concrete plant or a concrete product plant using a sieve or the like to collect fine powder containing cement hydrates and non-hydrated cement. Ready-mixed concrete sludge is easily carbonatable, and typically has a CaO content of 30 mass% or more. In addition, the waste concrete is preferably fine powder containing cement hydrate and non-hydrated cement, which is obtained by crushing concrete waste generated during the demolition of concrete structures, etc., and then removing aggregate from the crushed concrete. Fine powder of waste concrete is easily carbonated, and the CaO content is usually 15% by mass or more. The alkaline earth metal-containing material is usually in a powder form from the viewpoint of improving the strength development of the hydraulic composition.
[0026] The content of alkaline earth metals in the powdered cement-containing material (wherein alkaline earth metals other than those contained in the alkaline earth metal-containing material (in other words, alkaline earth metals contained in materials other than the alkaline earth metal-containing material contained in the powdered cement-containing material) include only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide) is 0.1 to 10 mass%, more preferably 0.2 to 8 mass%, and particularly preferably 0.5 to 6 mass%, calculated as oxide. If the content is less than 0.1 mass%, the strength development of the cement composition decreases. If the content exceeds 10 mass%, the initial strength development of the cement composition (for example, at 1 day of age) may decrease. In addition, when the powdered cement-containing material contains multiple alkaline earth metals (however, the alkaline earth metals other than the alkaline earth metals contained in the alkaline earth metal-containing material include only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide), the above content is the total content.
[0027] The above-mentioned components (i) to (ii) and components (v) to (vi) (described later) may contain periclase (MgO), magnesium hydroxide (Mg(OH)2), calcium oxide (CaO; particularly free calcium oxide), calcium hydroxide (Ca(OH)2), etc. The alkaline earth metal content includes these alkaline earth metals in addition to the alkaline earth metals contained in the alkaline earth metal-containing material. Incidentally, alkaline earth metals (e.g., calcium) dissolved in silicate minerals (e.g., belite, alite), aluminate phases, and ferrite phases, which are contained in components (i) to (iii) and components (v) to (vi), as well as alkaline earth metals such as gypsum (CaSO4) and calcium carbonate (magnesium oxide, magnesium hydroxide, calcium oxide, and alkaline earth metals other than calcium hydroxide), do not affect the effects of the present invention, or are present in such small amounts that they have almost no effect on the effects of the present invention. The contents of periclase (MgO) and magnesium hydroxide (Mg(OH)2) contained in components (i) to (ii) and components (v) to (vi) can be measured by X-ray diffraction (XRD) / Rietveld method or the like. The content of calcium oxide (CaO) or calcium hydroxide (Ca(OH)2) contained in components (i) to (ii) and components (v) to (vi) can be measured by X-ray diffraction (XRD) / Rietveld method or in accordance with "JCAS I-01-1997 (Method for Quantitative Analysis of Free Calcium Oxide)".
[0028] In addition, when magnesium is contained as an alkaline earth metal, the content of magnesium in the powdered cement content is preferably 1.0 to 10 mass%, more preferably 2.5 to 8.0 mass%, and particularly preferably 4.0 to 6.0 mass% in terms of oxide. If the content is 1.0 mass% or more, the strength development of the cement composition is further improved. If the content exceeds 10 mass%, the initial strength development of the cement composition (for example, at 1 day of age) may decrease. In addition, when calcium is contained as an alkaline earth metal, the content of calcium in the powdered cement content is preferably 0.8 to 10 mass%, more preferably 1.0 to 4.0 mass%, further preferably 1.2 to 3.0 mass%, and particularly preferably 1.5 to 2.0 mass%, calculated as oxide. If the content is 0.8 mass% or more, the strength development of the cement composition is further improved. If the content exceeds 10.0 mass%, the initial strength development of the cement composition (for example, at 1 day of age) may decrease.
[0029] [(v) Ingredient: Gypsum] The content of SO3 in the powdery cement composition is preferably 6.0 mass% or less, more preferably 0.5 to 5.0 mass%, further preferably 1.0 to 4.5 mass%, and particularly preferably 1.5 to 4.0 mass%. If the content is 6.0 mass% or less, the strength development of the cement composition can be further improved. In cases where the SO3 content in the powdered cement-containing material does not fall within the desired numerical range, such as when Portland cement clinker is used as component (i) or when the SO3 content in component (ii) is low, gypsum can be used as a material for the powdered cement composition in addition to components (i) to (ii) and (iv) in order to adjust the SO3 content in the powdered cement-containing material so that it falls within the above-mentioned numerical range. Examples of the type of gypsum are not particularly limited, and include, for example, natural gypsum dihydrate, flue gas desulfurization gypsum, phosphate gypsum, titanic gypsum, hydrofluoric gypsum, etc. These may be used alone or in combination of two or more. Examples of the form of gypsum (whether it is a hydrate or not) include gypsum dihydrate, gypsum hemihydrate, and anhydrous gypsum. These may consist of only one type, or may include two or more types. Furthermore, when the component (i) is a pulverized Portland cement clinker, the powdered cement-containing material preferably contains gypsum in addition to the components (i) to (ii) and (iv).
[0030] [(vi) Ingredients: Others] The powdered cement-containing material may contain other materials in addition to the above-mentioned components (components (i) to (ii) and (iv)) as necessary, within the scope of the object of the present invention. Examples of other materials that may be added as necessary include various admixtures such as fly ash, silica fume, and ground granulated blast furnace slag, and various powdered admixtures. The powdered cement-containing material may also contain an alkali metal. The content of other materials in the powdered cement-containing composition is preferably 30% by mass or less, and more preferably 20% by mass or less, from the viewpoint of strength development of the powdered cement-containing composition.
[0031] [(B) Component] The cement composition A contains an amine (iii) as the component (B). [Component (iii): Amine] Examples of the amine include chain amines such as alkanolamines, alkylamines, polyamines, and hydroxylamines, and water-soluble amines such as cyclic amines, etc. These may be used alone or in combination of two or more. Among these, from the viewpoints of improving the strength development and increasing the amount of fixed carbon dioxide, chain amines are preferred, and alkanolamines are more preferred. Here, the alkanolamine is an amine having an amino group and a hydroxyl group in the molecule. Examples of alkanolamines include monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, methyldiethanolamine, 2-amino-2-methyl-1-propanol, methyldiisopropanolamine, diethanolisopropanolamine, diisopropanolethanolamine, tetrahydroxyethylethylenediamine, N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine, tris(2-hydroxybutyl)amine, diglycolamine, etc. Among them, monoethanolamine, diethanol, and triisopropanolamine are preferred from the viewpoints of availability and improved strength development. These may be used alone or in combination of two or more.
[0032] An alkanolamine having a structure in which a part of the alkanolamine is bonded to a polymer may also be used. In addition, the alkanolamine may be a used alkanolamine obtained from a carbon dioxide recovery unit. In an amine-based carbon dioxide recovery unit for recovering carbon dioxide from exhaust gas from a factory or the like, a liquid containing deteriorated alkanolamine is usually discarded. However, in the present invention, the waste liquid can be effectively utilized. Alkanolamines are known as grinding aids and may be used as grinding aids as well.
[0033] The amount of the amine (B) relative to 100 parts by mass of the powdery cement-containing material (A) described above is preferably 0.001 to 5.0 parts by mass, more preferably 0.005 to 4.0 parts by mass, even more preferably 0.02 to 2.0 parts by mass, even more preferably 0.05 to 1.8 parts by mass, even more preferably 0.1 to 1.6 parts by mass, even more preferably 0.5 to 1.4 parts by mass, and particularly preferably 0.8 to 1.2 parts by mass. When the amount is 0.001 parts by mass or more, the amount of carbon dioxide fixed can be increased, and the strength development can be further improved. When the amount is 5.0 parts by mass or less, the fluidity of the hydraulic composition before hardening can be prevented from deteriorating. Moreover, the cement composition A is preferably in a powder form from the viewpoints of ease of transportation and production of the hydraulic composition.
[0034] [Method of manufacturing cement composition A] The method for producing the cement composition A is not particularly limited, and examples thereof include a method in which the materials such as the above-mentioned components (i) to (vi) are mixed to prepare a cement composition. The order in which the materials are mixed is not particularly limited, and examples thereof include (a-1) a method of simultaneously mixing pulverized Portland cement or Portland cement clinker, a pulverized product of a burned material containing C2S and C2AS, and an amine, (a-2) a method of simultaneously pulverizing and mixing Portland cement or Portland cement clinker and a burned material containing C2S and C2AS, and then mixing the resulting mixture with an amine, and (a-3) a method of simultaneously pulverizing and mixing Portland cement or Portland cement clinker, a burned material containing C2S and C2AS, and an amine. In particular, in the method (a-3) of simultaneously grinding and mixing Portland cement or Portland cement clinker, a burned material containing C2S and C2AS, and an amine, the amine also has an effect as a grinding aid. When the cement composition further comprises materials such as alkaline earth metal-containing materials, the materials are usually mixed simultaneously with the Portland cement or Portland cement clinker, the calcined product containing C2S and C2AS.
[0035] In addition, in a method for producing a hydraulic composition (described later) by kneading (mixing) a powdered cement-containing material obtained by previously mixing components (i) and (ii), component (iii), water, and aggregate, it is preferable that component (iii) is previously mixed with water to form an aqueous solution. In particular, when using used alkanolamine (waste liquid containing alkanolamine) obtained from a carbon dioxide capture device as component (iii), it is preferable to previously mix it with water in the above method. The amount of each material is determined so that the content of each material in the cement composition falls within a target numerical range. For example, the amount of the alkaline earth metal-containing material is determined by measuring the content of the alkaline earth metal in each material in advance, and then determining the content (oxide equivalent) of the alkaline earth metal in the cement composition (wherein the alkaline earth metal other than the alkaline earth metal contained in the alkaline earth metal-containing material includes only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide) within a target numerical range.
[0036] [Cement composition B] Another example of the cement composition of the present invention is a cement composition (hereinafter also referred to as "cement composition B") containing (i) pulverized Portland cement or Portland cement clinker, (ii) a pulverized sintered product containing 2CaO·SiO2 and 2CaO·Al2O3·SiO2, which satisfies the above-mentioned conditions (1) and (2), and (iv) an alkaline earth metal-containing substance, in which the content of alkaline earth metals in the cement composition (however, alkaline earth metals other than those contained in the alkaline earth metal-containing substance (in other words, alkaline earth metals contained in materials other than the alkaline earth metal-containing substance contained in the cement composition) include only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide) is 0.1 to 10 mass % in terms of oxide. It should be noted that the cement composition B does not contain the above-mentioned component (iii).
[0037] In cement composition B, (i) the ground Portland cement or ground Portland cement clinker, (ii) the ground fired product containing 2CaO SiO2 and 2CaO Al2O3 SiO2 which satisfies the above-mentioned conditions (1) and (2), and (iv) the alkaline earth metal-containing material may be the same as the components (i), (ii), and (iv) used in cement composition A, respectively. The content of Portland cement or pulverized Portland cement clinker in the cement composition B is preferably 10 to 60% by mass, more preferably 15 to 50% by mass, and particularly preferably 20 to 40% by mass. If the content is 10% by mass or more, the strength of the hardened body can be increased. If the content is 60% by mass or less, the content of (ii) the pulverized burned material becomes larger, and the reduction in carbon dioxide emissions described above can be further achieved.
[0038] In the cement composition B, the amount of the pulverized calcined product relative to 100 parts by mass of Portland cement or pulverized Portland cement clinker is preferably 30 to 500 parts by mass, more preferably 65 to 450 parts by mass, even more preferably 100 to 400 parts by mass, even more preferably 150 to 350 parts by mass, and particularly preferably 200 to 320 parts by mass. If the amount is 65 parts by mass or more, the amount of carbon dioxide absorbed by the hydraulic composition at the early age becomes larger. If the amount is 500 parts by mass or less, the strength development of the cement composition is less likely to decrease due to the relatively small amount of Portland cement or pulverized Portland cement clinker.
[0039] The content of the pulverized calcined product in the cement composition B is preferably 10 to 90% by mass, more preferably 30 to 85% by mass, even more preferably 40 to 80% by mass, even more preferably 50 to 80% by mass, and particularly preferably 60 to 80% by mass. If the content is 10% by mass or more, the amount of carbon dioxide absorbed by the hydraulic composition at the initial age is increased. If the amount is 90% by mass or less, the amount of Portland cement or pulverized Portland cement clinker is relatively small, which makes it difficult for the strength development of the cement composition to decrease. The ratio of the total amount of component (i) and component (ii) in cement composition B is preferably 80 mass% or more, more preferably 90 mass% or more, and particularly preferably 95 mass% or more, from the viewpoint of improving the strength development of the cement composition and increasing the amount of carbon dioxide absorption.
[0040] The content of alkaline earth metals in cement composition B (wherein alkaline earth metals other than those contained in the alkaline earth metal-containing material (in other words, alkaline earth metals contained in materials other than the alkaline earth metal-containing material contained in cement composition B) include only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide) is 0.1 to 10 mass%, more preferably 0.2 to 8 mass%, and particularly preferably 0.5 to 6 mass%, calculated as oxide. If the content is less than 0.1 mass%, the strength development of the cement composition decreases. If the content exceeds 10 mass%, the initial strength development of the cement composition (for example, at 1 day) may decrease. In addition, when the cement composition B contains a plurality of alkaline earth metals (however, the alkaline earth metals other than the alkaline earth metals contained in the alkaline earth metal-containing material include only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide), the above content is the total content.
[0041] The above-mentioned components (i) to (ii), component (v) (described later), and component (vi) (described later) may contain periclase (MgO), magnesium hydroxide (Mg(OH)2), calcium oxide (CaO; particularly free calcium oxide), calcium hydroxide (Ca(OH)2), etc. The alkaline earth metal content includes these alkaline earth metals in addition to the alkaline earth metals contained in the alkaline earth metal-containing material. Incidentally, alkaline earth metals (e.g., calcium) dissolved in silicate minerals (e.g., belite, alite), aluminate phases, and ferrite phases, which are contained in components (i) to (ii) and components (v) to (vi), as well as alkaline earth metals such as gypsum (CaSO4) and calcium carbonate (magnesium oxide, magnesium hydroxide, calcium oxide, and alkaline earth metals other than calcium hydroxide), do not affect the effects of the present invention, or are present in such small amounts that they have almost no effect on the effects of the present invention.
[0042] When the cement composition B contains magnesium as an alkaline earth metal, the content of magnesium in the cement composition B is preferably 1.0 to 10 mass%, more preferably 2.5 to 8 mass%, and particularly preferably 4.0 to 6 mass% in terms of oxide. If the content is 1.0 mass% or more, the strength development of the cement composition is further improved. If the content exceeds 10 mass%, the initial strength development of the cement composition (for example, at 1 day) may decrease. In addition, when the cement composition B contains calcium as an alkaline earth metal, the content of calcium in the cement composition B is preferably 0.8 to 10 mass%, more preferably 1.0 to 4.0 mass%, further preferably 1.2 to 3.0 mass%, and particularly preferably 1.5 to 2.0 mass% in terms of oxide. If the content is 0.8 mass% or more, the strength development of the cement composition is further improved. If the content exceeds 10.0 mass%, the initial strength development of the cement composition (for example, at 1 day of age) may decrease.
[0043] The content of SO3 in the cement composition B is preferably 6.0 mass% or less, more preferably 0.5 to 5.0 mass%, further preferably 1.0 to 4.5 mass%, and particularly preferably 1.5 to 4.0 mass%. If the content is 6.0 mass% or less, the strength development of the cement composition can be further improved. In cases where the SO3 content in cement composition B does not fall within the desired numerical range, such as when Portland cement clinker is used as component (i) or when the SO3 content of component (ii) is low, gypsum can be used as component (v) in addition to components (i) to (ii) and (iv) as materials for cement composition B in order to adjust the SO3 content in cement composition B to fall within the above-mentioned numerical range. In the cement composition B, as the gypsum (v), the same one as the component (v) used in the cement composition A can be used. When the component (i) of the cement composition B is ground Portland cement clinker, it preferably contains gypsum in addition to the components (i) to (ii) and (iv).
[0044] In addition to the above-mentioned components (components (i), (ii), (iv), and (v)), cement composition B may contain other materials (component (vi)) as necessary, within the scope of the object of the present invention. Other materials that may be mixed as necessary include various admixtures such as fly ash, silica fume, ground granulated blast furnace slag, and various powdered admixtures. In addition, the cement composition B may contain an alkali metal in addition to the alkaline earth metal. The content of other materials in the cement composition B is preferably 30% by mass or less, and more preferably 20% by mass or less, from the viewpoint of the strength development of the cement composition. Moreover, the cement composition B is preferably in a powder form from the viewpoints of ease of transportation and production of the hydraulic composition.
[0045] [Method of manufacturing cement composition B] The method for producing the cement composition B is not particularly limited, and examples thereof include a method of mixing each of the materials such as the above-mentioned components (i) to (ii) and (iv) to (vi) to prepare a cement composition. The order in which the materials are mixed is not particularly limited, and examples thereof include (i) a method in which pulverized Portland cement or Portland cement clinker, a pulverized product of a burned material containing C2S and C2AS, and a powdered alkaline earth metal-containing material are mixed simultaneously, (ii) a method in which Portland cement or Portland cement clinker, a burned material containing C2S and C2AS, and a lump of alkaline earth metal-containing material are mixed together, and (iii) a method in which Portland cement or Portland cement clinker and a burned material containing C2S and C2AS are mixed together, and then the mixture is mixed with the powdered alkaline earth metal-containing material. In addition, when grinding a burned material containing Portland cement or Portland cement clinker, C2S and C2AS, a grinding aid may be used. The amount of each material is determined so that the content of each material in the cement composition falls within a target numerical range. For example, the amount of the alkaline earth metal-containing material is determined by measuring the content of the alkaline earth metal in each material in advance, and then determining the content (oxide equivalent) of the alkaline earth metal in the cement composition (wherein the alkaline earth metal other than the alkaline earth metal contained in the alkaline earth metal-containing material includes only magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide) within a target numerical range.
[0046] [Hydraulic composition] The above-mentioned cement composition A or B can be hardened by containing water. An example of the hydraulic composition of the present invention contains the above-mentioned cement composition A, water, and aggregate, and the amount of water is 25 to 70 parts by mass per 100 parts by mass of the powdered cement-containing material (hereinafter, also referred to as "hydraulic composition A"). Another example of the hydraulic composition of the present invention contains the above-mentioned cement composition B, water, and aggregate, and the amount of water is 25 to 70 parts by mass per 100 parts by mass of the cement composition (hereinafter, also referred to as "hydraulic composition B"). In this specification, the term "hydraulic composition" includes both the fluid form before hardening and the form after hardening.
[0047] The water is not particularly limited, and examples thereof include tap water and recycled water as specified in "JIS A 5308:2019 (Ready Mixed Concrete)". In the hydraulic composition A, the amount of water per 100 parts by mass of the powdered cement-containing material is 25 to 70 parts by mass, preferably 30 to 65 parts by mass, more preferably 40 to 60 parts by mass, and particularly preferably 45 to 55 parts by mass. If the amount is less than 25 parts by mass, the fluidity of the hydraulic composition before hardening decreases. If the amount is more than 70 parts by mass, the strength of the hardened product of the hydraulic composition decreases. In the hydraulic composition B, the amount of water relative to 100 parts by mass of the cement composition B is 25 to 70 parts by mass, preferably 30 to 65 parts by mass, more preferably 40 to 60 parts by mass, and particularly preferably 45 to 55 parts by mass. If the amount is less than 25 parts by mass, the fluidity of the hydraulic composition before hardening decreases. If the amount is more than 70 parts by mass, the strength of the hardened body of the hydraulic composition decreases.
[0048] The aggregate may be fine aggregate alone or a combination of fine and coarse aggregates. In addition, any of natural aggregates, artificial aggregates, and recycled aggregates may be used. The fine aggregate is not particularly limited, and examples thereof include river sand, mountain sand, land sand, sea sand, crushed sand, silica sand, limestone fine aggregate, slag fine aggregate, lightweight fine aggregate, clinker fine aggregate, glass aggregate, and CCU fine aggregate (fine aggregate in which carbon dioxide is fixed to one or more selected from recycled aggregate, waste concrete, blast furnace slag, and steelmaking slag), etc. These may be used alone or in combination of two or more.
[0049] The coarse aggregate is not particularly limited, and examples thereof include river gravel, mountain gravel, land gravel, sea gravel, crushed stone, limestone coarse aggregate, slag coarse aggregate, lightweight coarse aggregate, clinker coarse aggregate, glass aggregate, and CCU coarse aggregate (coarse aggregate in which carbon dioxide is fixed to one or more selected from recycled aggregate, waste concrete, blast furnace slag, and steelmaking slag), etc. These may be used alone or in combination of two or more. When the hydraulic composition contains coarse aggregate, the fine aggregate ratio (volume ratio of fine aggregate / (fine aggregate+coarse aggregate) expressed as a percentage) is preferably 5 to 70%, more preferably 10 to 60%, and particularly preferably 20 to 50%. If the fine aggregate ratio is within the above range, the workability and ease of molding of the hydraulic composition before hardening are improved. The content of aggregate in the hydraulic composition A (the total amount when fine aggregate and coarse aggregate are used in combination) is preferably 200 to 750 parts by mass, more preferably 300 to 650 parts by mass, per 100 parts by mass of the powdered cement-containing material. The content of the aggregate in the hydraulic composition B (the total amount when fine aggregate and coarse aggregate are used in combination) is preferably 200 to 750 parts by mass, more preferably 300 to 650 parts by mass, per 100 parts by mass of the cement composition B. When the content is within the above range, the strength of the set body of the hydraulic composition becomes greater and the shrinkage rate of the set body becomes smaller.
[0050] The hydraulic composition may contain various admixtures such as cement dispersants (water reducing agents, AE water reducing agents, high performance water reducing agents or high performance AE water reducing agents), AE agents, defoamers, shrinkage reducing agents, organic fibers, glass fibers, etc., as necessary, within the scope that does not impair the object of the present invention.
[0051] When the hydraulic composition of the present invention is a carbonated hardened product obtained by carbonation (particularly, a hardened product obtained by carbonation curing), the strength of the hydraulic composition can be further increased. The carbonated hardened body can be obtained, for example, by subjecting the hydraulic composition to carbonation curing. Carbon dioxide is fixed in the hydraulic composition by carbonation curing, and the structure of the hydraulic composition is densified, thereby making it possible to increase the strength of the hydraulic composition. The carbonation curing method is not particularly limited, but examples thereof include a method of exposing the hydraulic composition to carbon dioxide for carbonation curing, and a method of blowing carbon dioxide into the hydraulic composition when kneading the hydraulic composition (in this case, a larger amount of carbon dioxide can be absorbed), etc. The carbonation of a hydraulic composition (other than carbonation curing) also includes a form in which carbonation occurs naturally by absorbing carbon dioxide in the air over a long period of time in the form of a concrete product, concrete structure, concrete pavement, or the like. The amount of carbon dioxide fixed per ton of cement composition is preferably 80 to 400 kg / ton, more preferably 100 to 350 kg / ton, even more preferably 150 to 330 kg / ton, still more preferably 200 to 315 kg / ton, and particularly preferably 250 to 300 kg / ton. If the amount of fixation is 80 kg / ton or more, the total amount of carbon dioxide discharged can be further reduced. If the amount of fixation is 400 kg / ton or less, productivity can be further improved.
[0052] [Method of manufacturing hydraulic composition] An example of a method for producing a hardened body of a hydraulic composition obtained by carbonation curing includes a method including a mixture preparation step of preparing a mixture, which is a mixture of the materials constituting the cement composition, water, and aggregate, a casting step of casting the mixture into a formwork, a demolding step of removing the hardened body of the kneaded material from the formwork after the kneaded material in the formwork has hardened, and a carbonation curing step of carbonating the hardened body of the kneaded material demolded from the formwork to obtain a carbonated hardened body. Each step will be explained in detail below.
[0053] [Kneaded material preparation process] This step is a step of preparing a kneaded product, which is a mixture of the materials constituting the cement composition, water, and aggregate. In the hydraulic composition A, the method for preparing a mixture, which is a kneaded product, using each material constituting the cement composition A, water, and aggregate is not particularly limited, and examples thereof include (a-1) a method of simultaneously kneading (mixing) a pre-prepared cement composition A, water, and aggregate, and (a-2) a method of simultaneously kneading (mixing) a powdered cement-containing product (A) obtained by previously mixing the components (i) to (ii) constituting the component (A), the component (B), water, and aggregate, and the like. In the hydraulic composition B, the method for preparing a kneaded product, which is a mixture of the materials constituting the cement composition B, water, and aggregate, is not particularly limited, and examples thereof include (b-1) a method of simultaneously mixing a pre-prepared cement composition B, water, and aggregate, and (b-2) a method of simultaneously mixing a pre-mixed mixture of the components (i) and (ii), the component (iv), water, and aggregate. The method for kneading the materials is not particularly limited. The device used for kneading is also not particularly limited, and for example, a commonly used mixer such as an omni mixer, a pan mixer, a twin-shaft mixer, or a tilting mixer can be used.
[0054] [Pouring process] This process is a process in which the mixture obtained in the previous process is poured into a formwork. The casting method is not particularly limited, and a conventional method such as casting can be used. The curing method used after pouring the kneaded material into the formwork and before demolding is not particularly limited, and for example, general curing methods such as air curing, moist air curing, underwater curing, sealed curing, and steam curing can be used. [Demolding process] This step is a step in which, after the kneaded mixture in the formwork has hardened, the hardened body of the hydraulic composition obtained by the hardening of the kneaded mixture is removed from the formwork.
[0055] [Carbonation curing process] This step is a step of carbonating the hardened hydraulic composition released from the formwork to obtain a carbonated hardened body by carbonating the hardened hydraulic composition. From the viewpoint of increasing the absorption of carbon dioxide in carbonation curing, the concentration of carbon dioxide gas in carbonation curing is preferably 1 vol% or more, more preferably 10 vol% or more, even more preferably 50 vol% or more, and particularly preferably 60 vol% or more. From the viewpoint of reducing the cost of curing equipment, etc., the concentration of carbon dioxide gas is preferably 95 vol% or less, more preferably 85 vol% or less, and even more preferably 80 vol% or less. The temperature in the carbonation curing is preferably 5 to 100°C, more preferably 10 to 90°C, even more preferably 15 to 80°C, even more preferably 20 to 75°C, even more preferably 25 to 70°C, even more preferably 30 to 65°C, even more preferably 30 to 50°C, and particularly preferably 30 to 40°C. If the temperature is 5°C or higher, the efficiency of carbonation is further improved and the strength of the hardened body is further increased. If the temperature is 100°C or lower, the energy cost required for the carbonation curing can be further reduced. The relative humidity in the carbonation curing is preferably 20 to 90%, more preferably 30 to 80%, and particularly preferably 40 to 70%. If the relative humidity is 20% or more, the efficiency of carbonation is improved and the strength of the hardened body is increased. If the relative humidity is 90% or less, the cost of curing equipment can be reduced. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [A. Production of the calcined product as component (ii)] Using sewage sludge, construction waste soil, limestone, and clay as raw materials, the raw materials were mixed so as to obtain a target chemical composition range including the chemical composition shown in Table 1 (actual measured values in the examples), and the raw materials were prepared for firing. The raw materials for firing were then fired at 1,370°C in a rotary kiln to obtain a fired product. In addition to heavy oil, waste oil and waste plastic were used as fuels for firing. Next, the fired product was pulverized, and the powder X-ray diffraction (XRD) pattern of the pulverized product was obtained using an X-ray diffractometer (manufactured by Bruker Japan, product name "D8 ADVANCE A-25 type"). The measurement conditions of the powder X-ray diffraction were as follows: target: CuKα, tube condition: 40 kV-40 mA, scanning range: 2θ = 5 to 65 °, step width: 0.023 ° / step, and measurement time: 0.13 seconds / step. The obtained powder XRD pattern was qualitatively analyzed using analysis software (manufactured by Bruker Japan, product name "DIFFRAC.EVA"), and peaks of C2S (β-C2S), C2AS, C3A, and CA were observed. On the other hand, no peak of MgO (periclase) was observed.
[0057] The mineral composition of the ground material was measured by fitting the theoretical profiles of the minerals C2S (β-C2S), C2AS, C3A, and CA to the measured profiles obtained from the powder XRD results by the Rietveld method using analytical software (manufactured by Bruker Japan, product name "DIFFRAC.TOPAS ver.6"). The results are shown in Table 2. The content of f.CaO in the fired product was measured in accordance with "JCAS I-01-1997 (method for determining free calcium oxide)" and was found to be 0.3 mass%. The calcined product did not contain Mg(OH)2 or Ca(OH)2. The Blaine specific surface area of the pulverized calcined material is 3,310 cm 2 / g.
[0058] [Table 1]
[0059] [Table 2]
[0060] [B. Preparation of hydraulic composition] [Materials used] (1) Cement: Ordinary Portland cement (Blaine specific surface area: 3,290 cm 2 / g); manufactured by Taiheiyo Cement Corporation; having the chemical composition shown in Table 3 and the mineral composition shown in Table 4; the chemical composition of the cement was measured in accordance with "JIS R 5204:2019 (Method for fluorescent X-ray analysis of cement)". No peak of periclase (MgO) was observed in X-ray diffraction. The mineral composition of the cement was measured in the same manner as the crushed material of the above-mentioned calcined material, except that the mineral setting of the analysis software was changed to the type of mineral shown in Table 4. The content of f.CaO of the cement measured in accordance with "JCAS I-01-1997 (Method for quantification of free calcium oxide)" was 0.2 mass%. The cement did not contain Mg(OH)2 or Ca(OH)2. (2) Burned products: the above (3) Gypsum: Excavated dihydrate gypsum (4) Amine A: Monoethanolamine (2-aminoethanol) (5) Amine B: Diethanolamine (2,2'-iminodiethanol) (6) Amine C: Triisopropanolamine aqueous solution (triisopropanolamine content: 85% by mass) (7) Amine D: 2-amino-2-methyl-1-propanol (8) MgO: Periclase (industrial reagent, MgO content: 95.0% by mass or more) (9) MgSO4·7H2O: Reagent (10) CaO: hard-burned quicklime (industrial reagent, CaO content: 93.0% by mass or more) (11) Fresh concrete sludge: Fresh concrete sludge was dried at 105°C as a pretreatment and then crushed. BET specific surface area: 14.71 m 2 / g, average particle size (frequency basis) 46.9 μm, 50% volume cumulative particle size (D50) 20.4 μm, chemical composition shown in Table 5 (measured in accordance with "JIS R 5204: 2019 (Fluorescent X-ray analysis method for cement)"), calcium hydroxide content 15.8 mass% (12) Fine aggregate: Cement Association standard sand
[0061] [Table 3]
[0062] [Table 4]
[0063] [Table 5]
[0064] [Examples 1 to 3] The calcined product and dehydrated gypsum were mixed and pulverized in amounts such that the mass ratio was 95.67:4.33 to obtain a mixture of the pulverized calcined product and dehydrated gypsum. The above mixture and ordinary Portland cement were mixed in a mass ratio of 75:25 (mixture: ordinary Portland cement) to obtain a powdered cement-containing material. The chemical composition (actual values) of the powdered cement-containing material is shown in Table 6, and the mineral composition (calculated values) is shown in Table 7. The chemical composition of the powdered cement-containing material was measured in accordance with JIS R 5204:2019 (Method for X-ray fluorescence analysis of cement). The mineral composition was measured in the same manner as for the pulverized product of the fired material. The Blaine specific surface area of the powdered cement-containing material was 3,300 cm 2 / g. Using the obtained powdered cement-containing material, the types of amines shown in Table 8, fine aggregate, and water in the amounts shown in Table 8 ("Water / powdered cement-containing material" in Table 8 indicates the mass ratio of water to the powdered cement-containing material), a test specimen was prepared in accordance with "JIS R 5201:2015 (Physical Testing Methods for Cement)" and demolded one day later. Carbonation curing was performed in a curing tank at a temperature of 65°C, a relative humidity of 60%, and a carbon dioxide concentration of 80% by volume. While performing carbonation curing, the compressive strength and flexural strength of the test specimen (hardened body of hydraulic composition) at a material age of 7 days (excluding the one day from preparation of the test specimen to demolding) were measured in accordance with "JIS R 5201:2015 (Physical Testing Methods for Cement)".
[0065] Specimens were prepared in the same manner as in the measurement of compressive strength and bending strength described above, and after demolding, they were subjected to carbonation curing in a curing tank at a temperature of 65°C, a relative humidity of 60%, and a carbon dioxide concentration of 20% by volume. After crushing the specimens at the time points of 3, 7, and 14 days of age, the amount of carbon in the specimens was measured using a carbon-sulfur analyzer, and the amount of carbon dioxide in the specimens (A) was calculated by converting the measured value into CO2. Next, the amount of carbon dioxide contained in the specimens before carbonation curing (B) was calculated based on the amount of carbon contained in each specimen (hardened body of hydraulic composition) measured using a carbon-sulfur analyzer and the blend ratio of the hydraulic composition, and the amount of carbon dioxide fixed in the specimens was calculated from the difference (AB) between the amount of carbon dioxide before carbonation curing and the amount of carbon dioxide after curing. The amount of carbon dioxide fixed (kg / ton) was calculated by dividing the amount of carbon dioxide fixed in the test specimen by the amount of cement used in the test specimen. In addition, after carbonation curing was performed for up to 3 days, the test specimens were removed from the curing tank and cured for an additional 4 days in a constant temperature and humidity room at a temperature of 20°C and a relative humidity of 60% (shown as "3 days + 4 days" in Table 8). The amount of carbon dioxide fixation of these test specimens was measured in the same manner.
[0066] [Comparative Example 1] The compressive strength, flexural strength, etc. of the hydraulic composition at an age of 7 days were measured in the same manner as in Example 1, except that no amine was used. The results are shown in Table 9.
[0067] [Table 6]
[0068] [Table 7]
[0069] [Table 8]
[0070] [Table 9]
[0071] From Table 9, the compressive strength of Examples 1 to 3 (55.9 to 68.2 N / mm 2 is the compressive strength of Comparative Example 1 (55.6 N / mm 2 ) is found to be larger than In addition, the bending strength at 7 days of the materials in Examples 1 to 3 (10.4 to 12.2 N / mm 2 ) is the bending strength of Comparative Example 1 at 7 days (10.4 N / mm 2 ) is similar to or better than the Furthermore, it can be seen that the amounts of carbon dioxide fixed in Examples 1 to 3 (3 day age: 232 to 236 kg / ton, 7 day age: 237 to 240 kg / ton, 14 day age: 239 to 247 kg / ton, 3+4 days age: 236 to 238 kg / ton) are greater than the amount of carbon dioxide fixed in Comparative Example 1 (3 day age: 227 kg / ton, 7 day age: 231 kg / ton, 14 day age: 234 kg / ton, 3+4 days age: 233 g / ton).
[0072] [Examples 4 to 8] The powdered cement-containing material prepared in Example 1 and the alkaline earth metal-containing material of the type shown in Table 10 were mixed in the amounts shown in Table 10 to obtain a cement composition. In Table 10, "content of alkaline earth metal" refers to the content of alkaline earth metal in the cement composition (converted into oxide). In addition, in Table 10, "derived from f·CaO" means f·CaO contained in the cement composition. Using the obtained cement composition (shown as "composition" in Table 10), fine aggregate, and water in the amounts shown in Table 10 ("water / composition" in Table 10 indicates the mass ratio of water to the cement composition), a test specimen was prepared in accordance with "JIS R 5201:2015 (physical test method for cement)". After demolding, the specimen was subjected to carbonation curing in a curing tank at a temperature of 30°C, a relative humidity of 60%, and a carbon dioxide concentration of 80% by volume. While carrying out carbonation curing, the compressive strength and flexural strength of the test specimens (hardened hydraulic composition) were measured at 3 and 7 days of age in accordance with "JIS R 5201:2015 (Physical testing methods for cement)". In addition, for specimens at 1 day, 3 days, and 7 days after carbonation curing in the same manner as for the measurement of bending strength, a 1% ethanol solution of phenolphthalein was sprayed onto the fractured cross section of the specimen after bending test, and the carbonation depth (the area colored by spraying the 1% ethanol solution of phenolphthalein) from the side (4 sides) of the specimen was measured using a vernier caliper, and the average value was taken as the carbonation depth (carbonation depth). In Table 11, "20.0 mm" indicates complete carbonation.
[0073] [Comparative Example 2] The compressive strength and flexural strength of the hydraulic composition at ages of 3 days and 7 days were measured in the same manner as in Example 4, except that no alkaline earth metal-containing substance was used. The results are shown in Table 11.
[0074] [Table 10]
[0075] [Table 11]
[0076] From Table 11, the compressive strength of Examples 4 to 8 (material age 3 days: 48.9 to 58.0 N / mm 2 , material age 7 days: 58.3~72.7N / mm 2 ) is the compressive strength of Comparative Example 2 (material age 3 days: 45.1 N / mm 2 , material age 7 days: 52.8N / mm 2 ) is found to be larger than In addition, the bending strength (10.1 to 12.5 N / mm) of Examples 4 to 6 and 8 at 3 days 2 ) is the bending strength of Comparative Example 2 at 3 days (9.8 N / mm 2 ) is found to be larger than Furthermore, the bending strength at 7 days of the materials in Examples 4 to 8 (12.1 to 14.8 N / mm 2 ) is the bending strength of Comparative Example 2 at 7 days (11.7 N / mm 2 ) is found to be larger than Furthermore, from the carbonation depth of Examples 4 to 8, it is found that the test specimens were carbonated to their insides at a material age of 3 days.
[0077] [Examples 9 to 12 and 14] A mixture of the pulverized calcined product and dehydrated gypsum prepared in Example 1 and a mixture of ordinary Portland cement (corresponding to the powdered cement-containing material in Example 1: shown as "powdered raw material" in Table 12) was mixed with amines of the types and amounts shown in Table 12 to obtain cement compositions. Using the obtained cement composition (shown as "composition" in Table 12), fine aggregate, and water in the amounts shown in Table 12 ("water / composition" in Table 12 indicates the mass ratio of water to the cement composition), a test specimen was prepared in accordance with "JIS R 5201:2015 (Physical Testing Methods for Cement)". After demolding, the specimen was subjected to carbonation curing in a curing tank at a temperature of 30°C, a relative humidity of 60%, and a carbon dioxide concentration of 80% by volume. While performing carbonation curing, the compressive strength of the test specimen (hardened body of hydraulic composition) at a material age of 7 days was measured in accordance with "JIS R 5201:2015 (Physical Testing Methods for Cement)".
[0078] Specimens were prepared in the same manner as in the measurement of compressive strength described above, and after demolding, they were subjected to carbonation curing in a curing tank at a temperature of 30°C, a relative humidity of 60%, and a carbon dioxide concentration of 20% by volume. The amount of carbon dioxide fixed (kg / ton) was calculated for the specimens at 3 and 7 days of age in the same manner as in Example 1. In Table 13, "-" indicates that no measurement was performed.
[0079] [Example 13] A powdered cement-containing material was obtained by mixing the mixture of the pulverized calcined product and dehydrated gypsum prepared in Example 1, a mixture of ordinary Portland cement, and an alkaline earth metal-containing material in the amount shown in Table 12. The obtained powdered cement-containing material was mixed with an amine of the type and amount shown in Table 12 to obtain a cement composition. In Table 12, "derived from f·CaO" means f·CaO contained in the powdered cement-containing material. Using the obtained cement composition, test specimens were prepared in the same manner as in Example 9, and the compressive strength of the test specimens at 7 days was measured in the same manner as in Example 9. In addition, in accordance with "JIS R 5201:2015 (Physical testing methods for cement)", the bending strength of the specimens was measured at 3 and 7 days of age. For the specimens at the time points of 3 days and 7 days after carbonation curing in the same manner as in the measurement of bending strength, the carbonation depth was measured from the sides (four faces) of the specimen in the same manner as in Example 4, and the average value was taken as the carbonation depth (carbonation depth). In Table 13, "20.0 mm" indicates complete carbonation. The results are shown in Table 13.
[0080] [Table 12]
[0081] [Table 13]
[0082] From Tables 9 and 13, it can be seen that the amount of carbon dioxide fixed at 7 days in Examples 9 to 12 and 14 (292 to 315 kg / ton) is greater than the amount of carbon dioxide fixed at 7 days in Examples 1 to 3 (which were subjected to carbonation curing in a curing tank at a temperature of 65°C, a relative humidity of 60%, and a carbon dioxide concentration of 20% by volume) (237 to 240 kg / ton). From Tables 11 and 13, the compressive strength at 7 days of Examples 9 to 14 (60.6 to 74.8 N / mm 2 ) is the compressive strength (7 days old: 52.8 N / mm2) of Comparative Example 2 (which does not use any amine or alkaline earth metal-containing material and is cured under the same conditions as Examples 9 to 14). 2 ) is found to be larger than In particular, the compressive strength of Example 13 (containing an amine and an alkaline earth metal) at 7 days (74.8 N / mm 2 ) is found to be the largest. Bending strength of Example 13 (material age 3 days: 11.8 N / mm 2, material age 7 days: 16.6N / mm 2 ) is the bending strength of Comparative Example 2 (material age 3 days: 9.8 N / mm 2 , 11.7N / mm 2 ) is found to be larger than From the carbonation depth of Example 13, it can be seen that the specimen was carbonated to its inside at the age of 7 days.
[0083] [Examples 15 to 16] A cement composition was obtained by mixing the mixture of the pulverized calcined product and dehydrated gypsum prepared in Example 1 with a mixture of ordinary Portland cement (corresponding to the powdered cement-containing material in Example 1: shown as "powdered raw material" in Table 14) with an alkaline earth metal-containing material of the type and amount shown in Table 14. In Example 16, two types of alkaline earth metal-containing materials were mixed. In Table 14, "Alkaline earth metal content" is the content of alkaline earth metals in the cement composition (converted into oxide). Using the obtained cement composition (shown as "composition" in Table 14), fine aggregate, and water in the amounts shown in Table 14 ("water / composition" in Table 14 indicates the mass ratio of water to the cement composition), a test specimen was prepared in accordance with "JIS R 5201:2015 (physical test method for cement)". After demolding, the specimen was subjected to carbonation curing in a curing tank at a temperature of 30°C, a relative humidity of 60%, and a carbon dioxide concentration of 80% by volume. While performing carbonation curing, the compressive strength of the test specimen (hardened body of hydraulic composition) at a material age of 7 days and the bending strength at each time point of material age of 3 days and 7 days were measured in accordance with "JIS R 5201:2015 (physical test method for cement)". For the specimens at the time points of 3 days and 7 days after carbonation curing in the same manner as in the measurement of bending strength, the carbonation depth was measured from the sides (four faces) of the specimen in the same manner as in Example 4, and the average value was taken as the carbonation depth (carbonation depth). In Table 13, "20.0 mm" indicates complete carbonation. The results are shown in Table 15.
[0084] [Table 14]
[0085] [Table 15]
[0086] From Tables 11 and 15, the compressive strength at 7 days of Examples 15 to 16 (53.5 to 56.9 N / mm 2 ) is the compressive strength (material age 7 days: 52.8 N / mm 2 ) is found to be larger than Examples 15 to 16 Flexural strength (3 days old: 10.3 to 11.5 N / mm 2 , material age 7 days: 11.6~13.1N / mm 2 ) is the bending strength of Comparative Example 2 (material age 3 days: 9.8 N / mm 2 , 11.7N / mm 2 ) is equal to or greater than From the carbonation depth of Examples 15 to 16, it can be seen that the test specimens were carbonated all the way to the inside.
Claims
1. (A) (i) Portland cement or ground Portland cement clinker, (ii) 2CaO.SiO 2 and 2CaO·Al 2 O 3 SiO 2 A ground product of a fired product comprising the above-mentioned, which satisfies the following conditions (1) to (2): (iv) A cement composition containing an alkaline earth metal-containing substance (limited to those other than (i) and (ii) above), The alkaline earth metal contained in the alkaline earth metal-containing material is magnesium (Mg), In the cement composition, the total content of free calcium oxide and the content of magnesium (Mg) contained in the alkaline earth metal-containing material in terms of oxide is 2.0 to 5.3 mass%, In the cement composition, the content of magnesium (Mg) contained in the alkaline earth metal-containing material is 1.7 to 5.0 mass% in terms of oxide, A cement composition, characterized in that the content of the pulverized calcined product (ii) in the cement composition is 60 to 80 mass %. (1) The above 2CaO.SiO 2 The above 2CaO·Al per 100 parts by mass 2 O 3 SiO 2 The amount of is 10 to 100 parts by mass. (2) The above fired product is 3CaO.Al 2 O 3 or does not contain the above 2CaO.SiO 2 Included in an amount of 15 parts by mass or less per 100 parts by mass
2. A hydraulic composition comprising the cement composition of claim 1, water, and aggregate, The hydraulic composition has an amount of the water of 25 to 70 parts by mass per 100 parts by mass of the cement composition.
3. further comprising (B)(iii) an amine, 2. The cement composition according to claim 1, wherein the amount of said amine is 0.5 to 2.0 parts by mass per 100 parts by mass of the total of said (i) and said (ii).
4. 4. The cement composition of claim 3, wherein said amine is an alkanolamine.
5. A hydraulic composition comprising the cement composition according to claim 3 or 4, water, and aggregate, The amount of the water is 25 to 70 parts by mass per 100 parts by mass of the total of the (i) and (ii).
6. A method for producing the hydraulic composition according to claim 2, comprising the steps of: a kneaded product preparation step of preparing a kneaded product, which is a mixture of the materials constituting the cement composition, the water, and the aggregate; A casting step of casting the kneaded mixture into a formwork; a demolding step of demolding the hardened body of the kneaded material from the mold after the kneaded material in the mold is hardened; The method for producing a hydraulic composition includes a carbonation curing step of carbonating the hardened body of the kneaded material released from the formwork to obtain a carbonated hardened body.
7. A method for producing the hydraulic composition according to claim 5, comprising the steps of: a kneaded product preparation step of preparing a kneaded product, which is a mixture of the materials constituting the cement composition, the water, and the aggregate; A casting step of casting the kneaded mixture into a formwork; a demolding step of demolding the hardened body of the kneaded material from the mold after the kneaded material in the mold is hardened; The method for producing a hydraulic composition includes a carbonation curing step of carbonating the hardened body of the kneaded material released from the formwork to obtain a carbonated hardened body.
Citation Information
Patent Citations
Cement admixture
JP2004002155A
Cement hardening body and manufacturing method therefor
JP2016047788A
Cement curing body and manufacturing method therefor
JP2016153357A
Producing method of cement mixture, mixed cement and carbon dioxide adsorbent
JP2021138574A
Cement clinker and cement
WO2008050484A1